Terra Sigillata Imports in Salacia (Alcácer do Sal, Portugal) - Viegas, Catarina (Rei Cretariae Romanae Fautorum Acta, 2015)
Alcácer do Sal is the Roman town of Salacia, located in the province of Lusitania, in the Sado estuary. Referring to the most important oppida along the today Portuguese coast, south from Olisipo (Lisbon), Pliny the Elder mentions, in its Historia Naturalis, Salacia (today Alcácer do Sal), Mirobriga (Chãos Salgados?), Ossonoba (Faro), Balsa (Torre de Ares-Tavira) and Myrtilis (Mértola). The geographic position of Salacia Urbs Imperatoria, in the Sado estuary, made it a strategic center both in the maritime and river bourn trade but also concerning the ancient road network.